Upaya Penerapan Manajemen Risiko dan Keselamatan Pasien Terhadap Peningkatan Mutu Pelayanan di Rumah Sakit: Systematic Literature Review - Aini, Wahyu Nur; Lailiyah, Syifa’ul; Kurniawati, Nurul Agustina (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Hospitals manage clinical governance well to be able to provide good and satisfying services for patients. Efforts to improve service quality in hospitals are related to risk management and patient safety. So, in writing this article to find out the relationship between the implementation of risk management and patient safety to improve the quality of hospital services. The research design used was Systematic Literature Review. The literature selection process uses the PRISMA method (Preferred Reporting Items for Systematic Review and Meta Analysis). Risk management and patient safety is a systematic effort to identify, analyze, evaluate and control dangerous risks to patients. Risk management control in hospitals is applied thoroughly and in various ways to maintain and improve the implementation of risk management and patient safety, as well as to support the improvement of service quality in the hospital. Improving the quality of health services in hospitals in implementing risk management and patient safety can be done by several things such as accreditation, implementing patient safety, implementing safety using patient safety goals (SKP) in SNARS (National Hospital Accreditation Standards), implementing surgical safety checklists, management support for the implementation of patient safety, support from government, leaders, and all hospital staff, awareness of patient safety, and monitoring and evaluation.